Absence of ethnic difference on single‐dose pharmacokinetics of rivoceranib between healthy male Caucasian, Japanese, and Chinese subjects. (9th November 2020) - Sachar, Madhav; Park, Cheol Hee; Pesco‐Koplowitz, Luana; Koplowitz, Barry; McGinn, Arlo
Abstract: Rivoceranib (known in China as apatinib) is a selective vascular endothelial growth factor receptor‐2 (VEGFR‐2) tyrosine kinase inhibitor which inhibits angiogenesis in solid tumors. The aim of study was to evaluate potential pharmacokinetic (PK) differences between the Caucasian, Japanese, and Chinese populations. An open‐label, single‐dose, parallel‐design PK study of rivoceranib was conducted in Caucasian, Japanese, and Chinese subjects. A total of 18 healthy males were recruited to each group (54 total), and 201 mg rivoceranib tablets (as 250 mg rivoceranib mesylate) were administered orally to subjects. Plasma samples were collected, and rivoceranib plasma concentration was determined using LC‐MS/MS. For PK analysis, non‐compartmental and compartmental analyses were performed. Intrinsic factors (CYP2C19 and CYP3A4 genotype) were also examined. Non‐compartmental analysis showed no significant difference in AUC0–t, AUC0–∞, Cmax, tmax, and t1⁄2 . Apparent clearance and volume of distribution were different across the three populations; however, the extent of this difference does not require dose modification. For compartmental modeling, a two‐compartment model was used to fit the plasma concentrations. No significant difference was observed in absorption, elimination, and intercompartmental transfer rate constants among the three groups. The present study shows no major ethnic PK differences between Caucasian, Japanese, and Chinese populations.